2011
DOI: 10.1111/j.1600-0579.2011.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making and treatment with respect to surgical intervention in the context of a European Core Curriculum in Cariology

Abstract: This paper is part of a series of papers towards a European Core Curriculum in Cariology for undergraduate dental students. The European Core Curriculum in Cariology is the outcome of a process starting in 2006 and culminating in a joint workshop of the European Organisation for Caries Research (ORCA) together with the Association for Dental Education in Europe (ADEE) which was held in Berlin from 27 to 30 June 2010. The present paper covers decision‐making and treatment with respect to surgical intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
(10 reference statements)
0
12
0
1
Order By: Relevance
“…Assimilation of general and tooth-specific information and integration of the best evidence is a complex process, and it goes without saying that obtaining, filtering and understanding scientific information are part of the process. Making a prognosis by judging the possible outcomes of a non-operative approach and scheduling appropriate recall periods allow dentist and patient to reappraise the clinical situation and outcome of a preventive approach and can redirect parts of the patient's treatment plan towards restorative treatment at the right moment if this proves necessary (5). Implementing non-surgical caries therapy needs a change in mentality and involves not only academia but also health politics and professional organisations.…”
Section: Resultsmentioning
confidence: 99%
“…Assimilation of general and tooth-specific information and integration of the best evidence is a complex process, and it goes without saying that obtaining, filtering and understanding scientific information are part of the process. Making a prognosis by judging the possible outcomes of a non-operative approach and scheduling appropriate recall periods allow dentist and patient to reappraise the clinical situation and outcome of a preventive approach and can redirect parts of the patient's treatment plan towards restorative treatment at the right moment if this proves necessary (5). Implementing non-surgical caries therapy needs a change in mentality and involves not only academia but also health politics and professional organisations.…”
Section: Resultsmentioning
confidence: 99%
“…As was observed in this study, related evidence‐based concepts for treatment of primary teeth, however, do not seem yet to be a central component of the education programmes at the undergraduate level in the analysed setting. The Association for Dental Education in Europe and the European Organisation for Caries Research, which synthesized the European Core Curriculum in Cariology for undergraduate dental students, suggested that decision‐making around surgical interventions for caries management has to be evidence‐based, focused on tooth preservation, in view of the short/long‐term success and failure rates of existing management approaches …”
Section: Discussionmentioning
confidence: 99%
“…The Association for Dental Education in Europe and the European Organisation for Caries Research, which synthesized the European Core Curriculum in Cariology for undergraduate dental students, suggested that decision-making around surgical interventions for caries management has to be evidence-based, focused on tooth preservation, in view of the short/long-term success and failure rates of existing management approaches. 29,30 For primary teeth, a restoration should ideally function until the tooth sheds naturally. Different studies, however, have shown failure rates of around 20%-30% for primary molar restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, undergraduate dental education has been widely discussed in many countries with the aim of modernizing the curriculum in cariology. Undergraduate dental education should enable students to become professionals with critical potential who are able to perform early diagnosis and have a wider understanding of the caries process according to the best scientific evidence available [3,4]. …”
Section: Introductionmentioning
confidence: 99%